Comparing reporting of abortions in three nationally representative surveys: methodological and contextual influences. Issue 3 (17th June 2019) - Scott, Rachel H; Bajos, Nathalie; Wellings, Kaye; Slaymaker, Emma
Abstract : Background: Abortions are known to be underreported in surveys. Previous research has found a number of ways in which survey methodology may affect respondents' willingness to disclose abortions. The social and political climate surrounding abortion may also create stigma affecting abortion reporting, and this may vary between countries and over time. Methods: We estimate the extent of underreporting in three nationally representative population surveys by comparing survey rates with routine statistics, in order to explore the ways in which survey methodology and cultural context might influence reporting of abortion. Data are analysed from two National Surveys of Sexual Attitudes and Lifestyles, conducted in 2000 and 2010 (Natsal-2 and Natsal-3) in Britain, and the Fertility, Contraception and Sexual Dysfunction survey (FECOND) conducted in 2010 in France. The three surveys differ with regard to survey methodology and context. Results: There was no strong evidence of underreporting in Natsal-2, which collected data on abortion using a direct question. There was evidence of underreporting in Natsal-3 and FECOND, both of which collected data on abortion through a pregnancy-history module. There was no evidence of a difference in the extent of underreporting between Natsal-3 and FECOND, which differed with regard to survey methodology (self-administered module in Natsal-3, telephone interview in FECOND) and country context. Conclusion: A direct question may be more effective in eliciting reports of abortion than a pregnancy-history module.